Translation methods of English-Indonesian subtitles in Mariana Atencio’s “TEDx talk: what makes you special?” - Iskandar; La Sunra; Nurul Aisyah (Center for Humanities and Innovation Studies, 2021)
This research aims at finding out methods used to translate connotative and denotative phrases in the video subtitle of Mariana Atencio’s “Tedx Talk: What Makes You Special?”. The video was translated to Indonesian by Badaruddin Saahe and has been reviewed by Santi Deviyanti Rahayu. This research method was qualitative descriptive, focusing on Newmark’s translation theory. The data of this research were taken from the transcript of the video and the provided subtitles. This study revealed twenty-eight phrases with connotative meaning, and the translation process employed both single and mixed methods. Single method types of translation employed were faithful translation, adaptation, free translation, and idiomatic translation, while mixed methods employed faithful and adaptation, faithful and semantic, faithful and communicative, adaptation and communicative, free and idiomatic, and idiomatic and adaptation. This study also revealed twelve phrases with denotative meaning, in which the translator chooses to translate them denotatively using various methods, despite the phrases conveying other meanings. This relates to the second study issue, which explains the connection between denotative meaningful sentences and Newmark (1988) translation approach. Following his observations, the researcher discovered that only one method was used: word-for-word and literal translation. To translate phrases with this denotative meaning, the translator employs two ways simultaneously: word-for-word and literal, literal and adaptation, literal & faithful, faithful & communicative, and Idiomatic & communicative. The researcher may deduce from the previous explanation that mixed techniques and denotative meaning are related in the sense that the combined methods share the same qualities, namely direct, contextual, and communicative. As stated by Fromkin (2001), this is also related to the properties of the denotation itself.